Health Status and the Demand for Healthcare among the Elderly in the Rural Quoc-Oai District of Hanoi in Vietnam. (24th September 2017) - Bang, Kyung-Sook; Tak, Sunghee H.; Oh, Juhwan; Yi, Jinseon; Yu, Soo-Young; Trung, Truong Quang
Abstract : Background . Vietnam is experiencing an unprecedented demographic transition. Its proportion of elderly people is growing rapidly. Objective . This study explored the health status and health-related quality of life (HRQoL) of rural elderly Vietnamese and assessed their needs for healthcare services. Design . This study used a survey with stratified proportion sampling and quota assignment. In 2016, data was collected from 713 people in the rural Quoc-Oai district of Hanoi aged 60 or older. Results . The mean age of the respondents was 70.9. Both self-rated health status and functional status decreased with age. Women reported more functional limitations than men. Musculoskeletal disorders were the most frequently reported chronic diseases, followed by hypertension, gastrointestinal diseases, and cardiovascular diseases. Age, self-rated health status, BMIs, and the number of noncommunicable diseases (NCDs) were found to be significant determinants of HRQoL, after controlling for socioeconomic effects. More than half the respondents requested more healthcare information, particularly on disease management. Conclusions . Vietnam's healthcare system is being challenged to make health services easily accessible and meet the growing needs for chronic illness management, risk reduction, promoting healthy lifestyles, and improving the aging population's quality of life.